A RAILWAY FUTURE PROJECT: PAKISTAN, AFGHANISTAN, AND UZBEKISTAN IN THE TWENTY-FIRST CENTURY - Muhammad Ismail (Galaxy International Interdisciplinary Research Journal, 2021)
Trade is vital for the concrete backbones of countries in the twenty-first century. Every country wishes to establish ties with other countries in order to increase exports and imports. Pakistan,Afghanistan, and Uzbekistan have agreed to collaborate on a multibillion-dollar train project that would improve trade between Central and South Asia. Pakistan, Afghanistan, and Uzbekistan have agreed on a strategic plan for a large railway project that would improve regional business and connectivity by providing direct access to the Arabian Sea for the landlocked region. The project would connect Pakistan’s Peshawar city with Afghanistan’s Kabul and Mazar-e-Sharif towns, as well as Uzbekistan, along a 573-kilometer railway track.Passenger and freight high-speed trains will be included in the trilateral project connecting Pakistan, Afghanistan, and Uzbekistan. After the Taliban took control of Kabul on 15 August 2021, the Taliban announced the end of the fighting and war in Afghanistan. The Taliban has stated that they want to have good relationships all around the world. The Taliban have pledged to defend every Afghan citizen. All schools, colleges, universities, banks, stores, airports, and hospitals are open to the Taliban. It indicates that after regaining control of the situation in Afghanistan, the Italian government would take action. After the Taliban government changes their ideology, the railway project across three nations will be a positive step forward in the future. The Taliban administration also maintains the trade project for exports and imports products.The project will open Pakistani seaports on the Arabian Gulf to Uzbekistan and continue Afghanistan’s gradual integration into the Central Asian economic system, which is expected to cost 5 billion.